2014
DOI: 10.9790/1959-03242730
|View full text |Cite
|
Sign up to set email alerts
|

Study on stress and coping strategies among private and government high school children in Udupi Taluk, Karnataka-A cross sectional study

Abstract: Introduction :Stress is experienced by adolescent in everyday life when they percieve situation which cannot be managed by them. Methodology : A cross sectional study has been conducted to measure the stress level and their coping mechanism to deal with such situations in Udupi Taluk.A total of 200 students were included in the study from private and government school. Result : The result shows that students likely to suffer from severe mental disorders are 3% in private school and 2 % in government school due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The knowledge of the prevalence and the variables affecting their health is of interest to policymakers for planning health and related welfare services at the institutional and community levels. The present study reveals that academic stress is prevalent among adolescents, a finding similar to studies in the region (Leeshma & Colaco, 2019;Nikitha et al, 2014;Tomar et al, 2014) and in India (Deb et al, 2014;Rentala, Nayak, et al, 2019;Roy et al, 2015;. The common stressors among adolescents showcased in a review (Chandan & Shivappa, 2020) were lack of competence, inability to cope with studies, disturbed family dynamics, peer pressure, and the lack of a robust support system (teachers, parents, and administrators).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The knowledge of the prevalence and the variables affecting their health is of interest to policymakers for planning health and related welfare services at the institutional and community levels. The present study reveals that academic stress is prevalent among adolescents, a finding similar to studies in the region (Leeshma & Colaco, 2019;Nikitha et al, 2014;Tomar et al, 2014) and in India (Deb et al, 2014;Rentala, Nayak, et al, 2019;Roy et al, 2015;. The common stressors among adolescents showcased in a review (Chandan & Shivappa, 2020) were lack of competence, inability to cope with studies, disturbed family dynamics, peer pressure, and the lack of a robust support system (teachers, parents, and administrators).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, three of the top-ranked stressors reported by adolescents with high stress were primarily external to the educational institution. Studies in the coastal region (Tomar et al, 2014;Verma, 2019) report that adolescents in higher secondary schools (public, private, and aided) used adaptive coping strategies, but their strategies differed. Measures specific to the individual and institutions in the region, such as awareness/education/ training programs for students, parents, and teachers, are necessary (Leeshma & Colaco, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation